Research-tool patents: issues for health in the developing world - Barton John H. (The World Health Organization, 2002)
The patent system is now reaching into the tools of medical research, including gene sequences themselves. Many of the new patents can potentially preempt large areas of medical research and lay down legal barriers to the development of a broad category of products. Researchers must therefore consider redesigning their research to avoid use of patented techniques, or expending the effort to obtain licences from those who hold the patents. Even if total licence fees can be kept low, there are enormous negotiation costs, and one "hold-out" may be enough to lead to project cancellation. This is making it more difficult to conduct research within the developed world, and poses important questions for the future of medical research for the benefit of the developing world. Probably the most important implication for health in the developing world is the possible general slowing down and complication of medical research. To the extent that these patents do slow down research, they weaken the contribution of the global research community to the creation and application of medical technology for the benefit of developing nations. The patents may also complicate the granting of concessional prices to developing nations - for pharmaceutical firms that seek to offer a concessional price may have to negotiate arrangements with research-tool firms, which may lose royalties as a result. Three kinds of response are plausible. One is to develop a broad or global licence to permit the patented technologies to be used for important applications in the developing world. The second is to change technical patent law doctrines. Such changes could be implemented in developed and developing nations and could be quite helpful while remaining consistent with TRIPS. The third is to negotiate specific licence arrangements, under which specific research tools are used on an agreed basis for specific applications. These negotiations are difficult and expensive, requiring both scientific and legal skills. But they will be an unavoidable part of international medical research.